Una Visión de la Eco-contabilidad desde la Cosmogonía del Pueblo Indígena Ampiuilʘ (2023)
In this research the main aspects of eco-accounting are understood, based on the qualitative study method, from the perspective of the three-dimensional theory of accounting focused on understanding their relationships from the eco and from the cosmogony of the Ampiuile indigenous people, a socio-cultural link, which generates a spiritual relationship from the environmental dimension and the representation of the fabric of life of collective family and community interaction, of the community of the department of Cauca in the municipality of Silvia.